Substantiation of survey procedures of the observation space in a systematic approach to the construction of a atmospheric monitoring radar system - Перелыгин, Б.В.; Боровская, Г.А.; Глушков, А.В. (Radiotekhnika, 2019)
When constructing a radar system for monitoring the atmosphere on the basis of a systematic approach, a method and technical means for the observation space survey are proposed to ensure high quality monitoring data, including the timing of the survey approaching the potential. Consideration is given to optimizing procedures of the observation space survey when deviating from the system approach when creating a system for radar monitoring of the atmosphere.